Viability Study of Trichoderma viride in Different Formulations at Different Temperatures - Manandhar, Shrinkhala; Baidya, Suraj; Manandhar, Chetana; Pant, Bimala (Journal of the Plant Protection Society, 2018)
Trichoderma is a well documented biocontrol agent of fungus origin being used for the control of various plant pathogens as people are being aware of the various detrimental effects of chemical pesticides. In Nepal also, the biocontrol agents are gaining popularity and there are several Trichoderma products in different trade names available in the market with label that they can be used within six months from the date of manufacture. However, it is very essential to know the fact that these microbial products contain living micro-organisms and therefore the conditions of storage for long term viability of the product should be given prior importance. This study was performed to find out the shelf life of Trichoderma viride based on various formulations and to know the effect of temperature on its viability. It was found that liquid based formulation and organic formulation had greater shelf life compared to talc based powder formulation. Also low temperature (4ºC) significantly increased the shelf life of the product (for over a year) while at ambient temperature conditions (15-25ºC), optimum viability of the biocontrol agent could be achieved only for a maximum of 3 months. Therefore it is important that farmers use fresh products and/ or store the products at cool and dark place to exploit the benefits of biopesticides.